Pengaruh Promo Aplikasi Myindihome terhadap Sikap Pelanggan Indihome Surabaya - Bagus Saputra Tricahyanto (Jurnal Spektrum Komunikasi, 2018)
As a company Telkom was accused to build customer loyality instead by improving sevice quality and adjusting the right strategy to deal with customer complain. Internet attendence recently was a big opportunity for company to upgrading the conventional way to become a fast and eficiently service. My indihome was build by PT.Telkom Indonesia as an online apps who believed to give a new way for better communication betwen company and customer by Customer Service Representative. In this research, researchers want to discover how much affect my indihome apps to customer Indihome Surabaya manner, with a 609.474 population of customer from January – December 2017 using database of Telkom Regional V Surabaya whose sampled by slovin formula with an error level 10% and the result are 100 respondents. Collecting methode was using survey and quesioner to gave accurate result for research. Result of analysis test show that My Indihome apps have a positive effect and significant for customer Indihome Surabaya. This was proven by t hitung 5.683 which is bigger than t tabel 1.664 so the hypothesis is accepted which mean my indihome apps effected positively and significantly to customer manner. Base on simple regresion liniear test amount 0,498 who included on middle category. This is because conventional services such as Plasa Telkom office and telephone service 031-147 still applied by Telkom to give extra service to customer Hard Complain.